Purkinje Cell Degeneration and Motor Coordination Deficits in a New Mouse Model of Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay - Ding, Man; Weng, Chao; Fan, Shanghua; Cao, Qian; Lu, Zuneng (Frontiers in Molecular Neuroscience, 2017)
Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset neurodegenerative disorder. In 2007, a novel locus, SAX2, which is located on chromosome 17p13 and contains 3 genes, ankyrin repeat and FYVE domain-containing 1 (ANKFY1), β-arrestin 2 (ARRB2) and kinesin family member 1C (KIF1C), was linked to ARSACS. We generated Ankfy1 heterozygous (Ankfy1/+) mice to establish an animal model and examine the pathophysiological basis of ARSACS. The transgenic mice displayed an abnormal gait with progressive motor and cerebellar nerve dysfunction that was highly reminiscent of ARSACS. These clinical features were accompanied by an early-onset and progressive loss of Purkinje cells, followed by gliosis. Additionally, the loss of Ankfy1 function resulted in an abnormal expression of neurotrophic factors (NTFs) in the Ankfy1/+ mouse cerebellum. Moreover, Purkinje cells cultured from neonatal Ankfy1/+ mice exhibited a shorter dendritic length and decreased numbers of dendritic spines. Importantly, cerebellar Purkinje cells from Ankfy1/+ mice and cells transfected with a lentiviral Ankfy1 shRNA underwent apoptosis. We propose that transgenic Ankfy1/+ mice are a useful model for studying the pathogenesis of ARSACS and for exploring the molecular mechanisms involved in this neurodegenerative disease.